Usefulness of serum androgen isotope ratio mass spectrometry (IRMS) to detect testosterone supplementation in women. Issue 4 (30th December 2022) - Andersson, Alexander; Piper, Thomas; Ekström, Lena; Hirschberg, Angelica Lindén; Thevis, Mario
Abstract: The detection of testosterone intake is facilitated by monitoring the urinary steroid profile in the athlete biological passport. This technique can be used with confidence to identify target samples for isotope ratio mass spectrometry. Regrettably, most research has been performed on male subjects resulting in a method that does not account for females' steroid concentration and/or variation. This study evaluates the usefulness of the carbon isotope ratio (CIR) in serum of female subjects. Two steroid sulphates are targeted in serum, androsterone and epiandrosterone. Both exhibit statistically significant depletion of their CIR after 10 weeks of daily (10 mg) transdermal testosterone administration. Of the 21 female subjects, samples from six individuals were identified as adverse analytical findings; additionally, four were found atypical considering the serum CIR. The urinary athlete biological passport was not sufficiently sensitive to identify target serum samples for isotope ratio mass spectroscopy. Of the six with a suspicious passport, only two could be confirmed using the serum CIR of androsterone and epiandrosterone. This study shows that CIR analysis in serum cannot be considered the sole confirmatory solution to detect testosterone doping in women due to low sensitivity. However, this analysis has the potential to be used as a complementary method in certain situations to confirm exogenous testosterone in women. Abstract : Isotope ratio mass spectrometry is used to differentiate endogenous androsterone and epiandrosterone from their naturally produced counterparts. This increases the analytical confidence when targeting female testosterone users.